Behavioral Study of RC Deep Beams Using Experimental Tests and Software Analysis (Architecture Image Studies, 2026)
This study uses nonlinear finite-element analysis in ANSYS and coordinated experimental testing to assess the structural response of M25-grade Conventional RC deep beams and Hybrid Fiber Reinforced Concrete (HFRC) deep beams. To determine load-deflection behavior, ultimate capacity, energy dissipation, simply supported deep beams were evaluated under two point loading. To simulate cracking and post-peak reaction, a calibrated concrete model with and without tri hybrid fibers in concrete mix was used. It was found that ANSYS prediction correlates reasonably well, validating the model. The value of energy dissipation in HFRC deep beam is about 50% higher than the conventional RC deep Beam specimen. Thus HFRC deep beam significantly improves energy absorption compared to conventional behavior. In comparison to control beams (conventional beam), HFRC deep beam specimens showed improved ductility, delayed diagonal cracking, energy dissipation and thus greater shear capacity.